Perhitungan Kadar Air, Rendemen dan Uji Organoleptik pada Ikan Asin : The Calculation of Moisture Content, Yield and Organoleptic Tests on Salted Fish - Nurfitriyani, Annisa; Triyastuti, Meilya Suzan; Shitophyta, Lukhi Mulia; Wahidi, Budi Rianto; Mukhaimin, Iman (Sam Ratulangi University, 2024)
Salted fish is a processed fishery product using salting and drying methods. Salted fish has a low moisture content because the salting process involves mass transfer by osmosis and drying involves heat transfer by solar radiation. This research aims to determine the moisture content, yield, and organoleptic tests on salted fish products using the dry salting method with varying salt concentrations of 10%, 20%, and 30%. The results of this study showed that the moisture content in each sample with a salt concentration of 10% (sample 1), 20% (sample 2), and 30% (sample 3) experienced a decrease in moisture content with the length of drying time for the fish. The lowest moisture content of salted fish in sample 3 with a salt concentration of 30%, was 6%. The longer the drying time for the fish and the higher the salt concentration in the fish, the lower the yield figures for each sample with concentrations of 10%, 20%, and 30%. In sample 1 the yield value obtained was 3% with a time of 414 hours, sample 2 was 3% with a time of 300 hours and in sample 3 the yield value was 3% with a time of 72 hours. For the organoleptic test results, the appearance aspect of sample 3 with a salt concentration of 30%, was highly favored by the panelists with an average value of (8.0); for the odor aspect of sample 1 with a salt concentration of 10%, the panelists liked it very much, obtaining a mean value of (8.3); For the taste and texture aspects, sample 3 got a mean score of 8.1 and 8.0 in the very like category. Meanwhile, for the fungal aspect in samples 1,2, and 3, the average value was 8.0, with the category of really liking the quality specifications, there was no fungus. The Salted fish products in this research are by the SNI standard no. SNI 8273:2016 concerning the maximum moisture content of salted fish of 40% and SNI no. 01-2346-2006 concerning the standard minimum organoleptic test value of least 7. Kata kunci: salted fish, moisture content, yield Ikan asin merupakan olahan hasil perikanan dengan menggunakan metode penggaraman dan pengeringan. Ikan asin mempunyai kadar air yang rendah karena proses penggaraman melibatkan perpindahan massa secara osmosis dan pengeringan melibatkan perpindahan panas dengan radiasi matahari. Penelitian ini bertujuan untuk mengetahui kadar air, rendemen dan uji organoleptik pada produk ikan asin menggunakan metode penggaraman kering dengan variasi konsentrasi garam 10%, 20%, dan 30%. Hasil dari penelitian ini menunjukkan bahwa kadar air pada masing-masing sampel dengan konsentrasi garam 10% (sampel 1), 20% (sampel 2) dan 30% (sampel 3) mengalami penurunan kadar air seiring lamanya waktu pengeringan pada ikan. Kadar air terendah ikan asin pada sampel 3 dengan konsentasi garam 30% yaitu sebesar 6%. Semakin lama waktu pengeringan ikan dan tingginya konsentrasi garam pada ikan, maka angka rendemen pada masing-masing sampel dengan konsentrasi 10%, 20% dan 30% pun semakin rendah. Pada sampel 1 nilai rendemen yang didapatkan adalah 3% dengan lama waktu 414 jam, sampel 2 pun 3% dengan lama waktu 300 jam, dan pada sampel 3 memiliki nilai rendemen 3% dengan lama waktu 72 jam. Untuk hasil pengujian organoleptik, pada aspek kenampakan sampel 3 dengan konsentrasi garam sebesar 30% sangat disukai panelis dengan nilai rata-rata (8,0); untuk aspek bau sampel 1 dengan konsentrasi garam sebesar 10% sangat disukai panelis dengan memperoleh nilai rerata (8,3); untuk aspek rasa dan tekstur sampel 3 endapatkan nilai rerata 8,1 dan 8,0 dengan kategori sangat suka. Sedangkan untuk aspek jamur pada sampel 1,2 dan 3 memiliki nilai rerata 8,0 dengan kategori sangat suka dengan spesifikasi mutu tidak terdapat adanya jamur. Produk Ikan Asin pada penelitian ini telah sesuai dengan standar SNI no SNI 8273: 2016 tentang kadar air ikan asin maksimum 40% dan SNI no 01-2346-2006 tentang standar nilai minimum pengujian organoleptik minimal 7. Kata kunci: ikan asin, kadar air, rendemen